The Evolving Trend Of Zeolite Applications In Water, Wastewater, And Leachate Treatment In Past 40 Years (1980-2020) - Lee, Wen Si (Universiti Sains Malaysia, 2021)
Zeolite is commonly used as an adsorbent to remove the pollutants in water, wastewater and leachate treatment through the adsorption and ion exchange mechanisms. However, not much work has been conducted to differentiate between the adsorption and ion exchange mechanisms, though they may occur concurrently. This study aims to review the adsorption and ion exchange mechanisms in water, wastewater and leachate treatment by using zeoliteas an adsorbent and/or ion-exchanger. The performance of the adsorption mechanism is affected by various parameters such as pH, adsorbent dose, contact time and initial concentration in the batch study. Many researchers found that Langmuir isotherm is the common adsorption isotherms found in zeolite, which is assumed to be monolayer adsorption. Many researchers also proved that the pseudo-second-order model is the common adsorption kinetics in zeolite to remove contaminants. However, the adsorption mechanism cannot be based on the simple fitting of the pseudo-second-order model, and further finding such as the intra-particles diffusion model need to be conducted. In the ion-exchange mechanism, the selectivity of ions is based on the charge density of the ions and the chemical composition of the zeolite. In the column study, flow rate and bed depth are the factors that would affect the removal efficiency of the pollutants in the experiment. The bibliometric analysis on the trends of zeolite application in water, wastewater and leachate treatment in the past 40 years (1980-2020) has also been conducted. From the Scopus database, 3782 papers had been published related to water, wastewater and leachate treatment. China is the most productive country among other countries on zeolite applications in water, wastewater and leachate treatment research. In the past 40 years, research on zeolite applications in water treatment has the highest number of publications compared to wastewater and leachate treatment. On the other hand, research on zeolite applications in leachate treatment is the lowest. By using VOSviewer software, the highest occurrence author keyword is the “zeolite”, followed by “adsorption” and “clinoptilolite”. Lastly, an overlay network was carried out to discern the hottest research trend. The range of the average publication year of the top 5 occurrences author keywords in water, wastewater and leachate treatment research are from year 2006 – 2014.